2021
DOI: 10.1007/s00284-021-02394-z
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Medicago sativa Crops Productivity by the Co-inoculation of Sinorhizobium meliloti–Actinobacteria Under Salt Stress

Abstract: Biotic and abiotic stresses are severely limiting plant production and productivity. Of notable importance is salt stress that not only limits plant growth and survival, but affects the soil fertility and threatens agricultural ecosystems sustainability. The problem is exacerbated in fragile arid and semi-arid areas where high evaporation, low precipitation and the use of salty water for irrigation is accelerating soil salinization. Legumes, considered very nutritious foods for people and providing essential n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 52 publications
1
16
0
Order By: Relevance
“…strain UW4 [ 109 ]. Similar observations were recorded in soybean inoculated with Arthrobacter woluwensis AK1 [ 18 ], Bacillus aryabhattai ALT29 [ 19 ] and Arthrobacter woluwensis ALT43 [ 19 ], and alfalfa co-inoculated of Arthrobacter strain M1, M2, and Nocardiopsis Ag-1 with rhizobium Sinorhizobium meliloti R1 and R2 [ 22 ].…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…strain UW4 [ 109 ]. Similar observations were recorded in soybean inoculated with Arthrobacter woluwensis AK1 [ 18 ], Bacillus aryabhattai ALT29 [ 19 ] and Arthrobacter woluwensis ALT43 [ 19 ], and alfalfa co-inoculated of Arthrobacter strain M1, M2, and Nocardiopsis Ag-1 with rhizobium Sinorhizobium meliloti R1 and R2 [ 22 ].…”
Section: Discussionsupporting
confidence: 73%
“…PGPA39 [ 14 ], maize inoculated with Azotobacter sp. C5 and C5 [ 97 ], and alfalfa inoculated and co-inoculated with Arthrobacter strains MS-1, MS-2, and symbiotic bacteria ( Sinorhizobium meliloti strains R1 and R2) [ 22 ]. Interestingly, plants inoculated with these actinobacteria showed growth performance that was not impaired by salt stress, in particular the dry weight and chlorophyll content.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PGPA39 contained lower proline content than non-inoculated tomatoes but exhibited higher dry biomass and chlorophyll content under salinity stress (180 mM NaCl). Similarity, inoculation and co-inoculation of Arthrobacter strain MS-1 and MS-2 with symbiotic bacteria (Sinorhizobium meliloti strains R1 and R2) decreased proline content in leaves and improved growth rate, number of nodules, and salt tolerance in alfalfa under salinity stress (100 mM NaCl) [39]. Therefore, our results suggested that D. barathri MT2.1 T may use another alternative approach in combination with proline accumulation to alleviate salinity stress.…”
Section: Promotion Of Tomato Growth Using Dermacoccus Strainsmentioning
confidence: 63%
“…Urea, as the N source in our experiment, was conducive to increasing P. bournei seedlings' nitrite absorption and reducing the nitrite content in the soil, thus decreasing Chloroflexi abundance, which oxidizes nitrites into nitrates, increasing autotrophic nitrite bacteria growth (e.g., the best Chloroflexi growth was in T2, which did not include N fertilizer) [41,42]. Actinobacteria are known to be beneficial bacteria that produce agricultural antibiotics and fight plant diseases [43]. Similar to most NPK fertilization results, high N levels resulted in reduced Actinobacteria abundance; however, an appropriate NPK ratio can promote Actinobacteria growth, reaching maximum abundance in T14 (N 2 P 1 K 1 ), probably because NPK fertilizer provides material and energy in relatively arid red soil [40,44].…”
Section: Soil Bacteria Response To Phoebe Bournei Seedlings' Npk Fertilizationmentioning
confidence: 90%